Protective effect of defibrotide on perfusion induced endothelial damage - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
In the present study, in vitro effects of Defibrotide (D) on perfusion-induced changes in the morphology of endothelium were investigated by scanning (SEM) and transmission (TEM) electron microscope. Human umbilical cord veins were incubated or perfused with platelet-rich plasma alone (PRP) or platelet-rich plasma with Defibrotide (PRP + D) at 3ml/min or 14ml/min and the changes observed were compared. SEM examination of luminal surfaces demonstrated that perfusion with high flow rates may damage endothelial cells and lead to morphological changes which may be prevented by the presence of Defibrotide in the perfusate, Also, the marked reduction in the number of adhered platelets on luminal surface of veins incubated or perfused with Defibrotide compared to veins treated with platelet-rich plasma only revealed that Defibrotide has anti-thrombotic effects. TEM examination of ruthenium red (RR) stained thin sections of veins demonstrated that perfusion disrupts the glycosaminoglcan (GAG) coat on endothelial cells. But the presence of D in the perfusate preserves the integrity of GAG, indicating further cytoprotective effects of the drug on endothelium. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: endothelium; defibrotide; ultrastructure; ORAL DEFIBROTIDE; REPERFUSION; ISCHEMIA; STIMULATION; CHOLESTEROL; DISORDERS; RABBITS; AGENT; HEART